2013
DOI: 10.1089/scd.2012.0401
|View full text |Cite
|
Sign up to set email alerts
|

Engraftment Potential of Spheroid-Forming Hepatic Endoderm Derived from Human Embryonic Stem Cells

Abstract: Transplantation and drug discovery programs for liver diseases are hampered by the shortage of donor tissue. While recent studies have shown that hepatic cells can be derived from human embryonic stem cells (hESCs), few cases have shown selective enrichment of hESC-derived hepatocytes and their integration into host liver tissues. Here we demonstrate that the dissociation and reaggregation procedure after an endodermal differentiation of hESC produces spheroids mainly consisted of cells showing hepatic phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…In our study, we employed day‐3‐induced DE cells as a source of isolated cells for transplantation into injured liver. The results showed DE cells were able to differentiate into hepatocyte‐like cells and attenuate AST and ALT levels after transplantation into injured liver, which confirmed the results of related reports 55, 56, 57. To our knowledge, this is the first report demonstrating that PEI‐MSNs can be used as a delivery system for growth factors to improve DE cells from mESCs in vivo and significantly restore liver function.…”
Section: Resultssupporting
confidence: 88%
“…In our study, we employed day‐3‐induced DE cells as a source of isolated cells for transplantation into injured liver. The results showed DE cells were able to differentiate into hepatocyte‐like cells and attenuate AST and ALT levels after transplantation into injured liver, which confirmed the results of related reports 55, 56, 57. To our knowledge, this is the first report demonstrating that PEI‐MSNs can be used as a delivery system for growth factors to improve DE cells from mESCs in vivo and significantly restore liver function.…”
Section: Resultssupporting
confidence: 88%
“…Recently, coculture of hiPSC-derived hepatocytes with human umbilical vein endothelial cells and human mesenchymal stem cells has been described to result in formation of 3D "liver buds" in vitro that could be efficiently engrafted and vascularized (53). Engraftment of spheroid-forming HLCs into CCl 4 -injured mice has also been described (54). Finally, two studies showed that human induced hepatocytes, transdifferentiated from human fibroblasts, could be engrafted in the liver parenchyma of transgenic mice and repopulate up to 0.3% to 4 Three months pi, all the inoculated HLC-engrafted mice showed high serum titers of HCV RNA (4-6 log [copies HCV RNA/ml]).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that primary hepatocytes and hiPSC-derived HLCs grown in 3D culture retain their hepatic features better when compared to their counterparts in 2D culture 74 75 76 77 78 79 80 81 . Most of the published protocols for the hepatic differentiation of hiPSCs or hESCs into HLCs have paired 2D culture during early stage of differentiation with subsequent 3D culture to promote assembly of differentiated cells for final maturation 32 78 82 83 84 85 86 . Our differentiation protocol was performed completely in 3D culture, using a new ROCKi-free and spin-free technique for EB formation 29 33 .…”
Section: Discussionmentioning
confidence: 99%